Sistem Informasi Keuangan Siswa Berbasis Web Mobile di RA Al-Irfan Purwakarta - Jalaludin, Jalaludin; Fatimah Zahra, Denada; Meilani , Anita (Rifa'Institute, 2023)
This Student Financial Information System is a system used to manipulate student financial data contained in an educational institution, with the aim of obtaining fast and accurate information for the purposes of a student financial information system at Raudlatul Athfal (RA) Al-Irfan Ciganea Purwakarta. Raudlatul Athfal (RA) Al-Irfan is a level of early childhood education (namely 6 years or below) in the form of formal education. Having a student financial information system which is considered to be still ineffective where the student financial information system still uses a manual system, and making reports takes quite a long time. This study aims to determine the current student financial information system, design the system, analyze and test the system as well as implement and build a student financial information system at RA Al-irfan Purwakarta. In developing this student financial information system, the authors used a structured approach method in which the data collection techniques used included observation and interviews. The development method uses a structured method with several tools and working techniques such as flowmaps, context diagrams, and data flow diagrams. For the development of this student financial information system, the authors use a mobile web-based application system, where the web can be accessed on computers and smartphones. Its supporting software is Xampp, CSS, HTML, MySQL, and PHP. The results of the study can be concluded that by building a student financial information system at Raudlatul Athfal (RA) Al-Irfan Ciganea Purwakarta, it is hoped that it can assist staff or employees in managing student financial data more effectively and efficiently, as well as minimizing errors in the process of making reports.